If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(12 + -1n) = 0 (12 * a + -1n * a) = 0 (12a + -1an) = 0 Solving 12a + -1an = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'a'. a(12 + -1n) = 0Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(12 + -1n)' equal to zero and attempt to solve: Simplifying 12 + -1n = 0 Solving 12 + -1n = 0 Move all terms containing a to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1n = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1n = 0 + -12 -1n = 0 + -12 Combine like terms: 0 + -12 = -12 -1n = -12 Add 'n' to each side of the equation. -1n + n = -12 + n Combine like terms: -1n + n = 0 0 = -12 + n Simplifying 0 = -12 + n The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
a = {0}
| 9z+4-7z=49-7z | | 2(-3p-6)=3[-4p-3(p+2)] | | 28+36+6(-7x+x)=2(5x-6) | | -4p-5=15 | | -16tx^2+21x-6=0 | | 6(a-8)+16=4(a-7) | | 6x-4(6-x)=2 | | Cot3x/5=-1 | | 28+36+6(-7x+c)=2(5x-6) | | 32+2x=12-7x | | 5(4x-2)+6=-3 | | 3(c-1)+4=17-(c-4) | | -8-5y-5=11-9y-16 | | -1=6-2(3y+2) | | 4x-50=4-5x | | A=x+3+z | | 4.5z=4.5z-6.25+6 | | 5x+19=x+21 | | 15-5x=-7x+15 | | 4x+16-6=22+6 | | 2y^2=13y | | 11=7+2(3z+2) | | -5x=-7+2x | | 7x+52=9x+24 | | 4m-33=11 | | 4cos^2(2t)-4sin^2(2t)=4 | | 4x-19=1x-30 | | 8z-3=-59 | | 9+(-6y)(3-y)+y^3=25 | | x^2-1=-3 | | 40x+10(1.5x)=719.47 | | 4-(2x+23)=29-8x |